2014
DOI: 10.1371/journal.pone.0111786
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Effects on Fungal Community Composition in the Wheat Phyllosphere

Abstract: The fungicides used to control diseases in cereal production can have adverse effects on non-target fungi, with possible consequences for plant health and productivity. This study examined fungicide effects on fungal communities on winter wheat leaves in two areas of Sweden. High-throughput 454 sequencing of the fungal ITS2 region yielded 235 operational taxonomic units (OTUs) at the species level from the 18 fields studied. It was found that commonly used fungicides had moderate but significant effect on fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
124
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 60 publications
(68 reference statements)
12
124
1
2
Order By: Relevance
“…In a greenhouse experiment, Liggitt et al, (1997) found that inoculation of wheat ears with saprotrophic fungi before F. culmorum inoculation reduced FHB severity. In the field, the phyllosphere of cereals harbour a diverse fungal community that is affected by cultural practices (Karlsson et al, 2014;Sapkota et al, 2015). Interactions between Fusarium and other fungi are likely to occur in the phyllosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In a greenhouse experiment, Liggitt et al, (1997) found that inoculation of wheat ears with saprotrophic fungi before F. culmorum inoculation reduced FHB severity. In the field, the phyllosphere of cereals harbour a diverse fungal community that is affected by cultural practices (Karlsson et al, 2014;Sapkota et al, 2015). Interactions between Fusarium and other fungi are likely to occur in the phyllosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The major difference between these two farming systems that is expected to affect fungal community structure is the application of fungicides. Previous studies have presented evidence of the effects of fungicide treatment on fungal community structure (13,16). Thus, we suggest that fungicide application might be one of the factors that differentiate the fungal community compositions between the extensive and conventional farming systems.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, Alternaria, Cladosporium, and Epicoccum are well known for their allergenic properties (7). Although the drivers of wheat phytopathogen infection, such as climatic factors, wheat cultivar, and cropping history, have been intensively studied (12), little is known about the factors that shape the structure of entire fungal communities (e.g., pesticides) (13), and even less is known about fungal diversity in airborne dust generated during wheat harvesting. Thus, currently the homogeneity of the exposure of grain workers to fungal aerosols from one field to another during their work is difficult to estimate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, selection 326 by the habitat can be exerted by agricultural practices. A few studies showed that fungicide 327 applications can reduce the diversity and alter the composition of the foliar microbial community 328 (Gu et al, 2010;Moulas et al, 2013; Cordero-Bueso et al, 2014;Karlsson et al, 2014). 329 However, several other studies showed that the foliar fungal communities of grapevine are 330 highly resilient to some chemical or biological pesticides (Walter et al, 2007; Perazzolli et al, 331 2014; Ottesen et al, 2015).…”
mentioning
confidence: 99%